2019
DOI: 10.1097/md.0000000000017422
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of computed tomography in prediction of operability of L5/S1 foraminal stenosis using region of interest

Abstract: Symptoms of intervertebral foraminal stenosis are caused by compression of nerve root exiting the intervertebral foramen. Many attempts to measure the size of the neuromuscular exit have been made; however, only a few studies to compare the area differences between foramens by computed tomography (CT) were done. In this retrospective comparative study, we used the region of interest (ROI) in CT to measure and compare the area of intervertebral foramen between the healthy control group and the patient group.Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Anatomical studies to supplement classical morphological teachings and improve treatment tactics for diseases of the cervical part of the vertebral column are still underway [19][20][21]. However, most authors who made lateral structures of the spine the subject of their scientific research either completely omitted intervertebral canals or their description did not include soft tissues and transverse processes of the vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical studies to supplement classical morphological teachings and improve treatment tactics for diseases of the cervical part of the vertebral column are still underway [19][20][21]. However, most authors who made lateral structures of the spine the subject of their scientific research either completely omitted intervertebral canals or their description did not include soft tissues and transverse processes of the vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that caudal cervical AP (from C5 to T1) were more frequently enlarged 5,9,14 . In companion animals and humans, the assessment of IF narrowing relies mainly on cross‐sectional imaging (CT or MRI) and various measurements have been described to objectively assess the dimensions of the IF; this includes the height, width, cross‐sectional area (CSA), and volume of the IF 15–24 . In humans, APCSA measured using MRI was a good predictor of cervical IF stenosis which was easy to use and fast to measure 25 .…”
Section: Introductionmentioning
confidence: 97%
“…In humans, APCSA measured using MRI was a good predictor of cervical IF stenosis which was easy to use and fast to measure 25 . CT measurement of IFCSA in sagittal plane have been proven useful for diagnosing and to help predicting the operability of people with lumbosacral IF stenosis 17 . In previous CT studies in horses, IF dimensions were assessed by measuring IF height or length 5,26 and AP dimensions were assessed by measuring their CSA, 5,11 but published studies assessing the IFCSA and the association between measurements of the AP and the size of the IF are still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations